2018
DOI: 10.1126/science.aap7607
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LZTR1 drive human disease by dysregulating RAS ubiquitination

Abstract: The leucine zipper–like transcriptional regulator 1 (LZTR1) protein, an adaptor for cullin 3 (CUL3) ubiquitin ligase complex, is implicated in human disease, yet its mechanism of action remains unknown. We found that Lztr1 haploinsufficiency in mice recapitulates Noonan syndrome phenotypes, whereas LZTR1 loss in Schwann cells drives dedifferentiation and proliferation. By trapping LZTR1 complexes from intact mammalian cells, we identified the guanosine triphosphatase RAS as a substrate for the LZTR1-CUL3 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
201
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(215 citation statements)
references
References 41 publications
12
201
2
Order By: Relevance
“…These disorders all result from dysregulation of RAS‐MAPK signalling so have collectively been termed the “RASopathies”. LZTR1 has only recently been functionally linked to RAS‐MAPK signalling, which explains why its role in NS long went unrecognised. For instance, the gene was absent from a list of 789 RAS–ERK pathway genes prioritised by Chen et al such that the pathogenicity of p.R237Q/p.A249P identified in that study was only realised subsequently .…”
Section: Discussionmentioning
confidence: 99%
“…These disorders all result from dysregulation of RAS‐MAPK signalling so have collectively been termed the “RASopathies”. LZTR1 has only recently been functionally linked to RAS‐MAPK signalling, which explains why its role in NS long went unrecognised. For instance, the gene was absent from a list of 789 RAS–ERK pathway genes prioritised by Chen et al such that the pathogenicity of p.R237Q/p.A249P identified in that study was only realised subsequently .…”
Section: Discussionmentioning
confidence: 99%
“…Human LZTR1 has been shown to interact with Cul3 in the Cul3 ubiquitin-ligase complex [27]. Cul3 in Drosophila has been associated with sleep and interacts physically in this regulation with Insomniac, another BTB/POZ-domain protein (like Nowl) that functions as a substrate adaptor in the Cul3 complex [15,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that LZTR1 may function in the Cul3 ubiquitin ligase complex to ubiquitinate Ras [27,28], which has previously been implicated in sleep regulation [54]. Nf1 is an important regulator of Ras signaling, and mutations in Nf1 and LZTR1 both give rise to types of neurofibromatosis [17,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, rates of protein synthesis, modification and degradation are tightly regulated and vary significantly between the cell type, tissue, and molecule in question. In contrast, disruption of normal proteome dynamics is thought to be a key component of the aging process, as well as being implicated in abnormal tissue development (Medina-Cano et al, 2018), and diseases (Steklov et al, 2018) such as inflammation (Yin et al, 2019), Alzheimer disease (Xia, 2019), skeleton dysplasia, cancer and fibrosis (Stegen et al, 2019) . However, our current understanding of how protein expression patterns are modified over time and how this varies between different body compartments is extremely limited.…”
Section: Introductionmentioning
confidence: 99%